Establishment of Coal-rock Constitutive Models for Numerical Simulation of Coal-rock Cutting by Conical Picks - Qiao, Shuo; Xia, Jingyi; Xia, Yimin; Liu, Zaizheng; Liu, Jinshu; Wang, Ailun (Periodica Polytechnica Civil Engineering, 2019)
One of the key points in numerical simulation of coal-rock cutting by conical picks is to select a proper coal-rock constitutive model. In order to find a reasonable coal-rock constitutive model, a uniaxial compression test was conducted to obtain the constitutive model. The several stages for linear elastic deformation and creep, plastic yielding, hardening, and finally brittle cracking of the constitutive units were studied, and the coal-rock constitutive model was established. As a result, the coal-rock cutting by one conical pick or two conical picks was simulated and the results were compared with coal-rock cutting experiment on a Coal-rock Cutting Machine. According to the simulation and experimental results, it is believed that the numerical simulation can reveal coal-rock crushing process. And the total error rate of coal-rock cutting by one conical pick between the simulation and experiment is 8.5%. The maximum deviation of coal-rock cutting by two conical picks between the simulation and experiment is 9.8%. All simulation values are within a reasonable range. The comparison indicates that the coal-rock constitutive model should better be defined considering the coal-rock crushing process by conical picks.